The 4th ICSSED, International Conference of Social Science and Education - Nursa'ban, Muhammad; Setiawan, Benni; Eko Agustinova, Danu; Trijuni Putro, Sutanto; Rahim, Robbi (De Gruyter, 2020)
The ICSSED is an academic conference that is centered on social science and education, is open and welcoming to contributions from the many disciplines and approaches that meet at the crossroads that is communication studies/methodological perspectives.